Foreign Direct Investment, Foreign Debt, Population Growth and Economic Growth in Somalia: A Co-Integration Analysis - Dalmar, Mohamed Saney; Ali, Ali Abdulkadir; Ali, Ali Yassin Sheikh (International Journal of Economics and Financial Issues, 2018)
This study aims to shed light on some of the key macroeconomic indicators that might improve Somalia’s real per capita economic growth. It also aims to verify the possible ways in which these factors could influence the formulation and implementation of economic policy. Specifically, it uses the Johansen test of co-integration to establish and assess a number of co-integrating variables that are related to economic growth and whether a long-run association between these variables and some of the major macroeconomic features of economic growth in Somalia can be established in these co-integration tests, without resorting to arbitrary normalization. The data range represents the period from 1991 to 2014. The augmented Dickey Fuller (ADF) technique is used to test the features of the time series in the data. The observed results show that almost all of the necessary variables were stationary (did not have a unit root), following their first differencing. Finally, it was found that there is at least one co-integrating equation among the variables in the model used in this study. For policy recommendations, the government administration is advised to seek possible alternative ways to internally generate more revenue and returns as opposed to becoming dependent solely on overseas support. Keywords: FDI, external debt, population, GDP, Johansen co-integration, Somalia JEL Classifications: Q56, H63, F43, C22 DOI: https://doi.org/10.32479/ijefi.7387